Face-to-Face or Flipped Learning Classroom: Which Method Enhances Iranian EFL Sixth-Grade Students’ Self-Efficacy in Virtual Learning Environment? - Vahid Norouzi Larsari; Farahman Farrokhi (Journal of Modern Research in English Language Studies)
The realm of education has experienced significant transformation driven by swift advancements in technology, leading to the rise of virtual learning as a key instructional approach. Within this context, the flipped classroom (FC) model has gained prominence as a modern, innovative methodology. This model inverts the traditional classroom structure, contrasting with conventional classroom practices by frequently incorporating instructional content through videos, or PowerPoint presentations. The study investigated the effect of FC model on sixthgrade students’ self-efficacy in Iran. Employing a quantitative research approach, 100 male sixth-grade students aged 12-13 were selected based on their Quick Oxford Placement test scores. Then, these participants were divided into a control group, experiencing traditional classroom teaching, and an experimental group, undergoing FC instruction using the Shad application platform. The study spanned two months, covering key English grammar objectives. Both groups took a pretest at the beginning, followed by 16 sessions of grammar instruction. A posttest assessed the teaching impact. Independent-samples t tests compared the two groups’ posttest mean scores. The findings demonstrated a significant performance improvement in the experimental group when compared to the control group. This suggests potential benefits for educators, policymakers, and institutions in adopting FC methods to improve academic literacy and student perceptions of virtual learning. Further research is recommended to evaluate the FC model’s long-term effects and adaptability across different educational settings.